"…де Хмельниченок лежить" (До питання останніх років життя та місця поховання Ю.Хмельницького) - Шумило, С.; Ластовський, В. (Український історичний журнал, 2022)
Мета статті – проаналізувати наявні версії щодо останніх років життя, смерті
й місця поховання українського гетьмана Юрія Хмельницького та спробувати визначити
найбільш реальну з них. Методологія дослідження ґрунтується на застосуванні принципів
історизму, системності, науковості, міждисциплінарності. Використано загальноісторичні
методи історіографічного аналізу, історико-генетичний, порівняльний. Наукова новизна
полягає в актуалізації в науковому обігу деяких історичних джерел, які раніше не бралися
до уваги. На їх основі здійснено спробу визначити імовірне місце смерті та поховання
Ю.Хмельницького. Висновки. На сьогодні впевнено можна стверджувати, що майже всі
версії щодо останніх років життя і смерті гетьмана виявилися хибними й безпідставними.
Детальний аналіз ряду джерел, у тому числі маловідомих для істориків, дозволяє стверджувати,
що його життя після відставки в 1681 р. закінчилося мирно, у сані ченця та, найімовірніше,
він був похований у місті Ґеліболу на Ґалліполійському півострові. Yu.Khmelnytskyi is one of the most controversial figures in Ukrainian history. As a
rule, in historical literature it is presented in a more negative light than positive. There are reasons
to assert the dominance of many myths related to the son of B.Khmelnytskyi in scientific works.
Nevertheless, detailed studies of the hetman’s biography have not yet been created. Many aspects
of his political activity, as well as the last years of his life, remain unexplained or erroneous.
The place of his burial is also a mystery. Today, there are no less than ten versions concerning the
death of Yu.Khmelnytskyi, and none of them are true. Documentary sources known today allow
us to reconstruct in more detail the last period of the hetman’s life and to express and substantiate
the idea about his actual burial place. The purpose of the article is to analyze the existing
versions regarding the last years of the life, death and burial place of the Ukrainian Hetman
Yu.Khmelnytskyi and to try to determine the most real of them. The research methodology
is based on the application of the principles of historicism, systematicity, scientificity, and
interdisciplinary. The following general historical methods were used: historiographical, historicalgenetic
and comparative analysis. Scientific novelty consists in the actualization in scientific
circulation of some historical sources that were previously not taken into account by historians.
Based on them, an attempt was made to determine the likely place of death and burial of
Yu.Khmelnytskyi. Conclusions. Today, it is safe to say that almost all the versions regarding the
last years of the life and death of the Ukrainian hetman Yu.Khmelnytskyi turned out to be false
and unfounded. Detailed analysis of a number of sources, including little known to historians,
allows us to assert that his life after his resignation in 1681 ended peacefully, in the sleigh of a
monk and, most likely, he was buried in the city of Gelibolu on the Gallipoli peninsula.